A Dynamic and Distributed Scheduling for Data Aggregation in Ubiquitous Sensor Networks Using Power Control. (27th May 2013) - Madhavi, S.; Kim, Tai Honn
Data aggregation scheduling in ubiquitous sensor networks is a major research interest for many researchers. Very little research is carried out to schedule the nodes in ubiquitous sensor networks for maximizing the throughput and utilize the hardware resources effectively. The traditional graph model does not model the interferences occurring from the concurrent transmissions in the Ubiquitous Sensor Networks. Hence in this paper we propose a new network model for the USN called a power control collision interference free model and a novel distributed data aggregation scheduling protocol which is adaptive to the rate and power. We tested the protocol in a USN consisting of 50, 100, 150, 200, and 250 number of nodes with different topologies and varying degree 2, 4, 6, 8, 10, 12, 14, 16, 18, 20, …, 40. We compared our results with the other protocols and proved that our proposed power control collision interference free model yields better results.